A Novel Functional Macrophage Differentiated from Monocytes by Co- Stimulation with IL-12 and IL-18 - Nascimento, Rute; Costa, Helena; Michael Evans Parkhouse, Robert; Bofill, Margarita (Current Immunology Reviews (Discontinued), 2013)
The pleiotropic cytokine IFN-γ is a key component controlling and linking intrinsic, innate and adaptive immune responses yet, only recently has its expression been definitively demonstrated in macrophages. Unlike macrophages generated from monocyte with M-CSF, those generated with IL-12/IL-18 are a functionally distinct IFN-γ and chemokine secreting, macrophage population. We therefore, propose that the interaction of pathogen-exposed macrophages with IL-12 and IL-18 at the early inflammatory site constitutes a critical and decisive event, in the orchestration of the immune response through the secretion of IFN-γ, prior to the arrival of activated NK and T cells. The chemokine profile of IL-12/IL-18 generated macrophage is interesting, not only attracting of monocytes and neutrophils to the inflammation, but also contributing to the wound healing process. Also, the ICAM-1 mediated aggregation of IL-12/IL-18 generated macrophages, may have relevance for granuloma formation. Stimulation of IFN-γexpression through IL-12 and IL-18 maybe particularly relevant in the lungs, an environment rich in IL-12 and IL-18, where macrophages constitute the first line of defense against airborn pathogens, and must function without inducing a dangerous inflammation. Indeed, an uncontrolled inflammatory responses can be fatal, and so the requirement for signaling via two unrelated signaling systems ( IL-12 and IL-18), may have evolved to provide suitable and flexible control. Finally, and in contrast to M1 or M2 macrophages, which are infectable with HIV-1, the IL-12/IL-18 population is resistant in an IFN-γ independent, SAMHD1 restriction factor dependent manner.
Keywords: innate immunity